Digital land : - Sipes, James L. (John Wiley & Sons, 2007)
It's your complete guide to design and planning as they relate to land and how digital technology fits into the process. Digital Land, Integrating Technology into the Land Planning Process, explains what digital tools are used to collect, assemble, and analyze information used to assess the suitability of both development and preservation. It also covers scales of planning -- including regional, community, and neighborhood projects -- and shows how digital tools can be used to complete those projects better and faster. Case studies offer sound examples of how digital and traditional tools were used in specific planning projects. This book is ideal if you make or are interested in decisions about the use of land in your neighborhood, community, or region.